(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Relevance : Pterygium is a pathological phenomenon, which is a triangular vascularized fold of the conjunctiva, progressing to the cornea, often localized on the nasal side. In the initial stages of the disease there are often no symptoms.